2008
DOI: 10.1002/app.28130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of silica‐, nanoclay‐ and carbon black‐filled EPDM rubbers

Abstract: Silica-, nanoclay-, and carbon black (CB)-filled ethylene-propylene-diene terpolymer (EPDM) mixtures were prepared and subsequently vulcanized. Rheological properties and cure characteristics of the mixtures and mechanical properties of vulcanizates were measured. Rheological property measurements indicated the storage modulus, loss modulus, and complex dynamic viscosity of silica-filled EPDM mixtures were much higher than those of CB-filled EPDM mixtures while tan d values were lower. The optimum cure time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…It is well known that silica has a vulcanization-retarding effect because it absorbs the curing activators and accelerators during processing. [25][26][27] However, in this study, it is obvious that WE compounds have shorter vulcanization times than do DE compounds. Table II gives the vulcanization parameters of WE and DE with or without ENR.…”
Section: Vulcanization Propertiesmentioning
confidence: 65%
“…It is well known that silica has a vulcanization-retarding effect because it absorbs the curing activators and accelerators during processing. [25][26][27] However, in this study, it is obvious that WE compounds have shorter vulcanization times than do DE compounds. Table II gives the vulcanization parameters of WE and DE with or without ENR.…”
Section: Vulcanization Propertiesmentioning
confidence: 65%
“…Rheological behavior of different filled polymer systems with carbon black and nanofillers was investigated by different researchers. 10,11 In one of our recent publications, we have reported a comparative study of dynamic and capillary rheology of pristine nanosilica-filled LDPE-EVA-based TPE system with variations in sequence of silica addition, their loading, and with the use of coupling agent. 12 We have also demonstrated the details of the dynamic rheological properties and capillary rheology of such system and have derived the correlation between them.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, silica has been introduced as a reinforcing filler for rubbers from economic factors and its ability to offer major functional benefits, such as low thermal expansion, chemical resistance, hard surface, high dielectric strength, etc., [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In fact, many studies have shown that the technical properties of silica reinforced compounds are better than those of carbon black filled ones [31][32][33][34][35][36][37]. Especially, silica is more often included in the compositions of vibration-damping and vibration-isolating rubber products.…”
Section: Introductionmentioning
confidence: 99%